STUDIES ON ANTIBACTERIAL EFFECTS OF BARK, SEED AND CALLUS EXTRACTS OF HOLARRHENA ANTIDYSENTERICA WALL. - MAHATO, SUCHITRA; ANITA MEHTA; ROY, SOMA (The Bioscan, 2013)
A procedure has been outlined for callus formation and antibacterial effects of bark, seed and callus extracts of an important medicinal shrub Holarrhena antidysenterica WALL. Explants used for callus formation were mainly seeds and both in vivo and in vitro grown plant parts like stem, nodal parts, roots and apical shoots. A friable type of callus was obtained when these explants were cultured on Murashige and Skoog (MS) culture medium containing different concentrations of 2,4-D separately and in combinations of KN. During present studies methanolic extracts of bark, seed and callus were made and tested for their antimicrobial activities against Staphylococcus aureus, Salmonella typhimurium and Eschercia coli. Results showed that all three different types of extracts of Holarrhena antidysenterica possess nearly similar potential for antibacterial activity against these pathogenic bacteria.